Synthesis, spectroscopic studies and X-ray structure determination of two mononuclear copper complexes derived from the Schiff base ligand N,N-dimethyl-N'-((5-methyl-1H-imidazol-4-yl)methylene)ethane-1,2-diamine - Haba, Pokpa; Sy, Adama; Tamboura, Farba Bouyagui; Sarr, Mamour; Thiam, Ibrahima Elhadji; Barry, Aliou Hamady; Sall, Mohamed Lamine; Gaye, Mohamed; Retailleau, Pascal (European Journal of Chemistry, 2019)
Reactions of the Schiff base N,N-dimethyl-N'-((5-methyl-1H-imidazol-4-yl)methylene) ethane-1,2-diamine (HL), synthesised in situ, with chloride or thiocyanate copper (II) salt; afforded two new mononuclear complexes, [Cu(HL)Cl2]·H2O (1) and [Cu(HL)(SCN)2] (2). These compounds have been studied and characterized by elemental analysis, IR and UV-Vis spectroscopies, electrochemistry, molar conductivity and room temperature magnetic measurements. Single crystal X-ray structure determination of the complexes revealed the presence of neutral moieties in the asymmetric unit. The mononuclear (1) crystallises in the monoclinic space group P21/c with the following unit cell parameters a = 7.4355(3) Å, b = 7.2952(3) Å, c = 26.2729(11) Å, β = 93.461(4)°, V = 1422.52(10) Å3, Z = 4, R1 = 0.033 and wR2 = 0.082 and the mononuclear complex (2) crystallises in the monoclinic space group C2/c with the following unit cell parameters a = 26.2578(7) Å, b = 7.4334(2) Å, c = 16.6237(5) Å, β = 99.089(3)°, V = 3203.95(16) Å3, Z = 8, R1 = 0.037 and wR2 = 0.104. In both complexes the ligand acts in tridentate fashion and the coordination environment of the copper atom can be described as distorted square pyramidal. The crystal lattice of the complex 1 is stabilized by electrostatic forces of attraction and O–H···Cl, C–H···O, N–H···Cl, and C–H···Cl, hydrogen bonding interactions while the crystal lattice of the complex 2 is stabilized by N–H···S and C–H···N.